ANALYSIS OF JUDGES' CONSIDRATIONS IN DECIDING CRIMINAL SANCTIONS AGAINST PEOPLE OF NARCOTICS ABUSE CRIMES IN MEDAN STATE COURT - Nasution, Rasina Padeni; Diningrum, Sekar Ayu; Siregar, Rahmat Insani; Saragih, Heny Aprilla; Matondang, Roy Andika Wiwara (ANAYASA : Journal of Legal Studies, 2024)
This study aims to determine and analyze the basic considerations of judges in the criminal verdict against drug criminals in the Medan District Court, knowing the factors that influence the judge's ruling against the perpetrators of particular crimes in violation of Article 127 Paragraph (1) and 112 Paragraph (2) of Law No. 35 of 2009 on narcotics. The data used is secondary data from the judge's decision. The analytical approach used is the approach and the concept of criminal law cases. These results indicate that the judge decided the case using the consideration of evidence as mentioned in the Criminal Code. The factors that influence the judge's decision cover three things, namely: the law of its own factor, the perpetrators factor, and the judge's concerned actors.